A companion to Asian art and architecture - Brown, Rebecca M.; Hutton, Deborah S. (Blackwell companions to art history, 2011)
"This companion presents new critical views on crucial aspects of the large and varied field of Asian art and architectural history. The essays collected here provide scholars and the pubic with an opportunity to engage with the field in all its diversity - from coinage to monastic spaces to imperial commissions and beyond. Regions and topics covered include Korea, Japan, China, several regions of Southeast Asia, South Asia, global and colonial interactions, as well as art and architecture in the UK and UK diasporas"--Provided by publisher.